The Prevalence and Awareness of Cardiovascular Diseases Risk Factors among the Lebanese Population: A Prospective Study Comparing Urban to Rural Populations - Iqbal Fahs; Zainab Khalife; Diana Malaeb; Mohammad Iskandarani; Pascale Salameh (Cardiology Research and Practice)
Introduction. CVDs are largely driven by modifiable risk factors. This study sought to determine the awareness and prevalence of the modifiable CVDs risk factors among the Lebanese population. Methods. In a cross-sectional survey, 1000 participants aged ≥ 45 years were randomly selected from pharmacies and interviewed. The data was analyzed with SPSS version 21.0 software. Results. Differences between urban and rural areas include alcohol consumption (2.8% versus 1.7%; p=0.0001), cardioprotective vegetable servings (6.1% versus 2.3%; p=0.016), sedentary hours per day (18.6% versus 15.1%; p=0.002), and hypertension (38.5% versus 25.4%; p=0.001). The prevalence of overweight and obesity (77.3% versus 75.2%; p=0.468), smoking (39.3% versus 43.3%; p=0.232), diabetes (25.4% versus 21.4%; p=0.173), and dyslipidemia (25 versus 21.2%) was reported. Measurements revealed 19.3% of undiagnosed hypertension (12.4% versus 22.4%, p=0.001), 61.7% of hypertension (59.8% versus 62.6%; p=0.203), and 7.9% of undiagnosed diabetes (6.6% versus 8.6%; p=0.323). The declared awareness of CVDs risk factors was highest for smoking (91.5% versus 89.7%; p=0.339) and lowest for diabetes (54.4 versus 55.7%; p=0.692). Conclusion. This study has shown a high prevalence of modifiable CVDs risk factors in the Lebanese population ≥ 45 years, among which hypertension is the most prominent.